Combined effects of warming and drought on plant biomass depend on plant woodiness and community type: a meta-analysis. Issue 1984 (12th October 2022) - Wilschut, Rutger A.; De Long, Jonathan R.; Geisen, Stefan; Hannula, S. Emilia; Quist, Casper W.; Snoek, Basten; Steinauer, Katja; Wubs, E. R. Jasper; Yang, Qiang; Thakur, Madhav P.
Abstract : Global warming and precipitation extremes (drought or increased precipitation) strongly affect plant primary production and thereby terrestrial ecosystem functioning. Recent syntheses show that combined effects of warming and precipitation extremes on plant biomass are generally additive, while individual experiments often show interactive effects, indicating that combined effects are more negative or positive than expected based on the effects of single factors. Here, we examined whether variation in biomass responses to single and combined effects of warming and precipitation extremes can be explained by plant growth form and community type. We performed a meta-analysis of 37 studies, which experimentally crossed warming and precipitation treatments, to test whether biomass responses to combined effects of warming and precipitation extremes depended on plant woodiness and community type (monocultures versus mixtures). Our results confirmed that the effects of warming and precipitation extremes were overall additive. However, combined effects of warming and drought on above- and belowground biomass were less negative in woody- than in herbaceous plant systems and more negative in plant mixtures than in monocultures. We further show that drought effects on plant biomass were more negative in greenhouse, than in field studies, suggesting that greenhouse experiments may overstate drought effects in the field. Our results highlight the importance of plant system characteristics to better understand plant responses to climate change.